2020
DOI: 10.1021/acs.jpcc.0c03623
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Electrolyte Solutions with Dipolar Cations on a Charged Electrode: Theory and Computer Simulations

Abstract: The development of advanced electrochemical devices for energy conversion and storage requires fine tuning of electrode reactions, which can be accomplished by altering the electrode/solution interface structure. Particularly, in case of an alkali-salt electrolyte the electric double layer (EDL) composition can be managed by introducing organic cations (e.g. room temperature ionic liquid cations) that may possess polar fragments. To explore this approach, we develop a theoretical model predicting the 1 arXiv:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The presence of static polarizability or a permanent dipole moment on the cations makes their attraction to the negatively charged electrode stronger than that of nonpolarizable anions to the positively charged electrode surface. The stronger attraction of the cations to the electrode is the result of an additional dielectrophoretic attractive force acting on the induced or permanent dipole placed in an inhomogeneous electric field 4,17,23 . Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of static polarizability or a permanent dipole moment on the cations makes their attraction to the negatively charged electrode stronger than that of nonpolarizable anions to the positively charged electrode surface. The stronger attraction of the cations to the electrode is the result of an additional dielectrophoretic attractive force acting on the induced or permanent dipole placed in an inhomogeneous electric field 4,17,23 . Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The authors introduced a new length scale related to the excess ion polarizability of ions and showed that when it is comparable to the effective Debye length, ion static polarizability can significantly influence double layer properties. It is also important to discuss several papers [20][21][22][23] , where the static polarizability or permanent dipole moment of ions were taken into account in the context of the theory of liquid electrolytes on charged interfaces. In paper 20 , the author incorporated ion static polarizabilities into the Poisson-Boltzmann equation by modifying the effective dielectric constant and the Boltzmann distribution of ions and thus formulated the so-called polarizable Poisson-Boltzmann equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified PB equations obtained up to now take into account the individual properties of ionic species and the chemical specifics of the surface interacting with them. In this case it is necessary to especially emphasize the consideration of the non-zero size of ions (steric interactions) [1][2][3][4] , their specific and structural interactions 5,6 , polarizability/quadrupolarizability and permanent dipole moment of ionic species and solvent (co-solvent) molecules [7][8][9][10][11][12][13][14][15][16][17] , surface charge regulaton 18 , specific ion-electrode interactions 12,19 and electrostatic correlations [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…It is significant that for the 5 case of the ideal ionic gas reference model, self-consistent field equation ( 8) transforms into the known polarizable PB equation [41]. We also mention that similar formalism [42] was also utilized to describe a two-component electrolyte solution on a charged electrode, where one of the cations possesses a sufficiently large dipole moment. Using the first integral of the self-consistent field equation, which is reduced to the condition of the RTIL mechanical equilibrium, and the expression for the surface charge density σ = (0)E(0), the authors obtained the following analytical expression for the DC…”
mentioning
confidence: 99%